2015
DOI: 10.5137/1019-5149.jtn.16276-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Paragangliomas of the spine

Abstract: Clinical presentations and courses of spinal paragangliomas are varied, and there are no standard principles of treatment to date (1,8). In this article, we report the clinical data of 7 consecutive cases with complete medical records and followup results that were treated in our institutions, in an attempt to explore the diagnosis, treatment and prognosis. █ mATERIAl and mEThODSA retrospective analysis was performed in 7 patients with spinal paraganglioma in our hospital from October 2000 to October 2011. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Continued follow-up for these patients shows a recurrence rate of 2.2% in the literature. Multiple studies reported a recurrence after complete resection in their case series in at least one patient, whereas others reported none [ 4 , 5 , 9 ]. Subtotal resection, however, can increase the figure substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Continued follow-up for these patients shows a recurrence rate of 2.2% in the literature. Multiple studies reported a recurrence after complete resection in their case series in at least one patient, whereas others reported none [ 4 , 5 , 9 ]. Subtotal resection, however, can increase the figure substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Paraganglioma's can be secretory secreting catecholamines, and patients presenting with hypertension, tachycardia or diaphoresis which weren't present in our case so we excluded functional or malignant paragangliomas 5 and we didn't go for catecholamines levels or other investigations in that direction. On the basis of location they can also present with mass effect like numbness, pain or weakness [6][7][8] . Our patient's MRI lumbosacral had also revealed a lesion extending from T12-L1 levels, so we thought that patient's symptoms of numbness, pain and weakness were due to that mass.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's MRI lumbosacral had also revealed a lesion extending from T12-L1 levels, so we thought that patient's symptoms of numbness, pain and weakness were due to that mass. Radiologically they appear hyperintense on T2 weighted images and iso or hypointense on T1 images of MRI 6,7,8 . These findings are consistent with MRI findings of our case which also showed a hyperintense area on T2 weighted images and hypointense on T1 weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies looking at malignant spinal paragangliomas in juvenile patients is lacking due to the extremely low incidence rate, and only 3 cases of juvenile patients have been reported in literature. [9,25] In a review of the literature, we discuss the common perioperative considerations in patients with malignant paragangliomas in the thoracic spine level and how to manage the perioperative hemodynamic complications. The epidemiology, origins, diagnosis, treatment, and prognosis of malignant spinal paraganglioma are also discussed.…”
Section: Introductionmentioning
confidence: 99%